Meeting the psychosocial needs of students with hearing impairment through counselling services (2013)
Adolescents with hearing impairment are often viewed as psychologically and socially maladjustment by all and sundry. This could be as a result of the inability of the environment to meet their psychological and social needs. Consequently, they have low sense of belonging in the society. Although, various scholars have attempted to address the psychosocial needs of students with hearing impairment through various strategies. This paper addressed the meeting of the psychosocial needs of students with hearing impairment though counselling services. It is strongly believed that counselling services in our schools will help students with hearing impairment to be aware of the various opportunities that will help them to adjust to their environment maximally.